Molecular characterisation of NPM1 and FLT3-ITD mutations in a central South African adult de novo acute myeloid leukaemia cohort - Jean F. Kloppers; André de Kock; Johané Cronjé; Anne-Cecilia van Marle (AOSIS, 2021)
Background: Recognition of molecular abnormalities in acute myeloid leukaemia (AML) has improved our understanding of its biology. NPM1 and FLT3-ITD mutations are recurrent in AML and clinically significant. NPM1 mutations are associated with a favourable prognosis, while FLT3-ITD mutations are an independent poor prognostic factor in AML. Objective: This study described the prevalence and molecular characteristics of the NPM1 and FLT3-ITD mutations in a newly diagnosed AML patient cohort in central South Africa. Methods: The study included 40 de novo AML patients. An NPM1 and FLT3-ITD multiplex polymerase chain reaction assay was optimised to screen patients for the respective mutations and were confirmed using Sanger sequencing. The prevalence of the NPM1 and FLT3-ITD mutations were determined, and mutation-specific characteristics were described in relation to patients' demographic information and AML classifications. Results: The patients' median age was 38.5 years, with 77.5% (n = 31) of patients being self-proclaimed Black Africans. AML with recurrent genetic abnormalities was most prevalent (57.5%; n = 23), of which acute promyelocytic leukaemia (APL) was most common (40.0%; n = 16). None of the patients had the NPM1 mutation. FLT3-ITD was present in 37.5% (6/16) of APL patients and in one (20.0%) of five AML patients with a t(8;21) translocation. Most patients had an FLT3-ITD allele ratio of ≥ 50% and ITD lengths of 39 bp. Conclusion: FLT3-ITD mutations were mainly found in APL cases at a similar prevalence as reported in the literature. High FLT3-ITD allele ratios and long ITD lengths predominated. No NPM1 mutations were detected.